Performance Evaluation of Road Transport Corporations: A Data Envelopment Analysis Approach - Vishnu C.R. and Regi Kumar V. (International Journal of Innovative Research in Science, Engineering and Technology, 2014)
This paper focus is on framing general benchmarking models for the road transport corporations using the technique of Data Envelopment Analysis (DEA). This is the first attempt for a DEA study on performance of road transport corporations. For the purpose of analysis two more Road Transport Corporations in South India where selected other than Kerala State Road Transport Corporation (KSRTC) where, KSRTC is regularly hitting the headlines with the reports of huge financial loss every year. The nearby Tamil Nadu State Transport Corporation (TNSTC) and Karnataka State Road Transport Corporation (KSRTC) are performing extremely opposite by making huge profits. Various variables concerning the efficiency of transport corporations where identified first to carry out Financial statement analysis a general mathematical model. This case study pinpoints the areas where Kerala SRTC needs to concentrate to improve its standard. Although the focus of this paper is in the above three corporations, much of the approach can be generalized for any number of transport corporation in any context for the purpose of benchmarking.